The study of the influence of workplace environment on job performance of staff at Pejabat Agama Daerah Hulu Terengganu / Farah Hana Fauziah Azmi - Azmi, Farah Hana Fauziah (Faculty of Business Management, 2017)
This research study will be discussed on the study of the relationship between workplace environment and employees' job performance. The study aims to measure employees' workplace environment satisfaction and job performance and to analyze the effect of workplace environment satisfaction towards job performance in Pejabat Agama Daerah Rulu Terengganu. Workplace environment can have brought the employees' satisfaction in the job performance. Because of the population size were small, it cannot give a better result which better workplace environment will improve employees' job performance or satisfaction in Pejabat Agama Daerah Rulu Terengganu. For future research, the suggestion is to have wide range of sample size to know which workplace environment has a least satisfaction.